Assessing the Distribution and Sustainable Exploitation of Lophius litulon in Marine Areas Off Shandong, China - Zhang, Zhaopeng; Wang, Yuanchao; Liu, Shude; Liang, Cui; Xian, Weiwei (Frontiers in Marine Science, 2022)
In recent years, the proportion and economic value of Lophius litulon (family Lophiidae) landed in China’s coastal fishery off Shandong Province have increased. In this study, we mapped the distribution of L. litulon abundance (catch per unit effort; CPUE), and applied a generalized additive model (GAM) to explore the relationship between its CPUE and environmental factors. Furthermore, two data-limited methods (the BSM related to CMSY method and the AMSY method) were used to evaluate the stock status and relevant fishery reference points of L. litulon. The results showed that the L. litulon stock was concentrated in the central Yellow Sea, at 34.0°–37.0° N and 121.0°–124.0° E, and the highest average CPUE of L. litulon in this area appeared in winter. The three most significant environmental factors affecting the species’ abundance were bottom temperature (BT), bottom salinity (BS), and depth (D). Lophius litulon was most abundant where BT ranged from 5.8°C to 10.6°C, D was >18 m, and BS varied from 31.0‰ to 33.2‰. BSM and AMSY model results indicated that the L. litulon stock was unhealthy and had been overfished in recent years, as its biomass remained below the level that can support maximum sustainable yield (MSY), and the relative exploitation ratios were high. This research will be of great significance to supplement the basic data of L. litulon and protect this fishery resource reasonably.